THE STRATEGIC MANAGEMENT OF CREATION PROCESS AND OF CHANGE: A THEORETICAL CONTRIBUTE FROM THE PERSPECTIVE OF TOURISM - Bruno Sousa (European Scientific Journal, ESJ, 2014)
The entrepreneurship and innovation have been gradually gaining ground in the academic community as a field of study. However, the interpretations surrounding fragmented, without a univocal definition. In last decades, tourism has received greater attention from researchers in various sciences, varying only by the different emphases considered: economic, social, cultural and environmental. As other emerging sectors in a modern economy, tourism is a dynamic and ever-changing industry. The study has as purpose to provide a better understanding regarding the essence of entrepreneurship: theoretical and practical implications from the perspective of tourism. Regarding the methodology used here, this is a conceptual paper with a literature review that brings together the major components of entrepreneurship and its implications tourist perspective and conceptual model of the dynamic nature of the Triggering Process and innovation (e.g. iTravey, Interactive Stores, Tourist Transportable Tower).